Hubungan antara Kurang Energi Kronik dengan Siklus Menstruasi - Eka Nurhasanah; Diding Kelana Setiadi; Ayu Prameswari (Jurnal Keperawatan Florence Nightingale, 2024)
Chronic energy deficiency (CED) hurts young women even into the next phase of life, one of which is hormonal imbalance which can affect the menstrual cycle. Riskesdas data show that women aged 15-19 years are in first place with the highest proportion of KEK. This study aims to identify the relationship between CED and the menstrual cycle among female students at SMKN 2 Sumedang. The methodology applied is a quantitative approach with a correlational survey design with a descriptive retrospective approach. The research sample included 178 female students who were identified as having CED using total sampling. Data was collected through a menstrual cycles questionnaire which was proven to be valid (r count > r table) and reliable (P = 0.720), while CED was measured using a LILA measuring tape. Data analysis was carried out univariately and bivariately using the chi-square test for non-parametric nominal data. The results of the analysis show that there is a significant correlation between CED and the menstrual cycle where the p-value <0,001. Based on the findings, it can be concluded that there is a relationship between CED and the menstrual cycle of female students at SMKN 2 Sumedang, this shows the importance of maintaining nutritional balance as a preventive measure for CED and the impacts it can cause.